Comparison of Nutritional Status of Hospitalized Patients in Gastroenterology Ward At Admission and During Discharge - Ali Haider, Salahuddin Mohammed; Paul, Binoy; Mohsin, Mostafa Noor; Ul Islam, Syed Mahtab; Ahmed, Ershad Uddin; Sarker, Md Khalequzzaman; Raihan, A S M A (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Malnutrition is a state of nutrition in which a deficiency and excess of energy, protein and other nutrients causes measurable adverse effects on tissue or body function and clinical outcome. The aim of study were to find out proportion of malnutrition during hospital admission and to observe the change of nutritional status of the patients during hospital stay. Materials and methods: This is a serial cross sectional study performed at Gastroenterology Department of Bangabandhu Sheikh Mujib Medical University, Dhaka during a period of May to December 2009. The nutritional status was assessed using Body Mass Index (BMI) and Mid Arm Circumference (MAC). Statistical analysis was performed using SPSS program and simple frequency distribution table. 202 patients were included in this study, 114 were male and 88 were female. 32 patients were over 60 years of age. Results: Out of 202 patients, 57 patients had chronic liver disease (28.2%) 44 patients had intestinal tuberculosis (21.8%) 18 patients had intestinal lymphoma (8.9%) 30 patients had GI malignancy (14.9%) and 53 patients had others gastrointestinal disorders (26.2%). Prevalence of malnutrition during hospital admission was 32.7%. Out of 202 patients, 66 patients (32.7%) were found to be malnourished at 1st day of hospital admission whereas 83 patients (41.1%) were malnourished at the time of discharge. Lowest recorded BMI was 14.8 and highest was 28.4 (19.9 mean ± 2.9 SD) whereas lowest recorded MAC was 15 and highest MAC was 34 (22.8 mean ± 3.4SD) during hospital admission. 14% patients had very poor appetite. Out of 145 patients who were hospitalized for 14 days or less, 34 (23.4%) and 32 (22.1%) patients had significant decreased MAC and BMI respectively. Out of 57 patients admitted for more than 14 days, 24 patients (42.1%) had significant decrease in BMI whereas 14 patients (24.6%) had significant decrease in MAC. Conclusion: Nutritional status of the patients during hospital stay has changed significantly in relation to disease pattern JCMCTA 2020 ; 31 (1) : 19-25